(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article states that studying the motives for choosing a future profession and the dynamics of learning motives in the process of mastering a specialty makes it possible to adjust learning motives and influence the professional development of students. The desire for success may be based on a special personality trait - the desire to test oneself or affirm the value of one’s personality, or the desire to achieve a socially significant result, the desire to create something necessary for people. Youthful maximalism also has a great influence on the professional aspirations of young people.